2015
DOI: 10.3892/ol.2015.4043
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ErbB2 renders breast cancer cells susceptible to 3-BrPA through the increased dissociation of hexokinase II from mitochondrial outer membrane

Abstract: Abstract. ErbB2 is known to upregulate glycolysis in breast cancer, however, the precise mechanisms remain unclear. In the present study, ErbB2 upregulated Hexokinase II (HK II) activity by increasing the binding of HK II to the mitochondrial outer membrane. Dysregulated glucose metabolism in high ErbB2-expressing breast cancer cells induces susceptibility to glucose starvation and glycolysis inhibition. Additionally, HK II has a tendency to dissociate from the mitochondria outer membrane in ErbB2-overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Protein structural analysis showed that this mutation was located in the P region (phosphorylation In keratinocytes, hSPCA1 not only transports Ca 2+ , but also competitively transports one Mn 2+ from the cytoplasm to the Golgi apparatus, which is nonreplaceable by other calcium pumps. It is known that the cells are very sensitive to Mn 2+ concentration and a slight change of Mn 2+ concentration may affect cell metabolism seriously [16]. Excessive intracellular Mn 2+ may prevent Mg 2+ binding to proteins, compromise the fidelity of DNA polymerase, and disrupt the transport function of cell membranes, thus affecting the physiological conditions of human body [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Protein structural analysis showed that this mutation was located in the P region (phosphorylation In keratinocytes, hSPCA1 not only transports Ca 2+ , but also competitively transports one Mn 2+ from the cytoplasm to the Golgi apparatus, which is nonreplaceable by other calcium pumps. It is known that the cells are very sensitive to Mn 2+ concentration and a slight change of Mn 2+ concentration may affect cell metabolism seriously [16]. Excessive intracellular Mn 2+ may prevent Mg 2+ binding to proteins, compromise the fidelity of DNA polymerase, and disrupt the transport function of cell membranes, thus affecting the physiological conditions of human body [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the ErbB2 signaling is a critical pathway involved in PD, which was in line with the reported studies. 43,74,75 Accordingly, western blot results showed that ErbB2 pY-1248 protein expression was dramatically upregulated in the cellular PD model. In contrast, there was no apparent change in the protein expression of ErbB1 and ErbB2.…”
Section: Discussionmentioning
confidence: 99%
“…In keratinocytes, hSPCA1 not only transports Ca 2+ , but also competitively transports one Mn 2+ from the cytoplasm to the Golgi apparatus, which is nonreplaceable by other calcium pumps. It is known that the cells are very sensitive to Mn 2+ concentration and a slight change of Mn 2+ concentration may affect cell metabolism seriously [16]. Excessive intracellular Mn 2+ may prevent Mg 2+ binding to proteins, compromise the delity of DNA polymerase, and disrupt the transport function of cell membranes, thus affecting the physiological conditions of human body [17,18].…”
Section: Discussionmentioning
confidence: 99%